Early Clinical Experience Module: Single Medical School Experience During the Pandemic - Safuraa Salihan; Mohamed Hanief Khalid; Azmah Sa’at; Chong Kok Wah; Shamala Devi Subramaniam (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2024)
Indexed by SCOPUS/MYCITE